Pengaruh Teknik Marmet terhadap Kelancaran ASI pada Ibu Postpartum di Wilayah Kerja Puskesmas Mowewe Tahun 2021 - Ismawati Ismawati; Aisyah Aisyah; Zulhaedah Zulhaedah (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
The marmet technique is a technique used to express breastmilk. This technique provides a relaxing effect and also reactivates the milk ejection reflex (MER) so that milk begins to drip. With the MER activated, breast milk will often spray out by itself. The marmet technique is a massage using two fingers. This method is often referred to as back to nature because it is simple and does not require cost. The purpose of the study was to determine the effect of the marmet technique on the smoothness of breast milk in postpartum mothers in the working area of the Mowewe health center in 2021. This type of pseudo-experimental research uses a nonequivalent control group design model. The research sample was the experimental group who were given treatment with marmet massage techniques on postpartum mothers as many as 10 people and the control group was those who were not given marmet massage treatment on postpartum mothers as many as 10 people. The results showed that there was no effect of marmet technique on the smoothness of breast milk in postpartum mothers in the working area of Mowewe health center. The difference between the average pretest and posttest in the control group using the paired sample t-test test obtained a t value = 3.240 and a p value = 0.010 (p < 0.05). It is hoped that the results of the study will serve as a source of information and add insight into the marmet method for smooth breastfeeding for postpartum mothers.